ANALYZING THE CONNECTION BETWEEN WRITING TOOLS AND ETHICS IN THE QUR'AN - Sayed Fitri Adhi; Muzakkir; Safria Andy (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir)
This study examines the relationship between writing tools and ethical values as articulated in the Qur'an, emphasizing the underlying spiritual and moral dimensions. Writing tools are not merely physical instruments for recording ideas but hold symbolic significance tied to human moral and spiritual responsibility. This research employs a Sufi approach and the theory of mun?sabah (thematic coherence of verses) as interpreted by Fakhruddin Ar-Razi and Quraish Shihab to explore how the Qur'an perceives the act of writing. The findings reveal that the Qur'an elevates the significance of writing tools as symbols of trust, honesty, and piety, playing a crucial role in shaping individual and societal ethics. This study offers new insights into integrating spiritual values into literacy practices, transforming writing into not only an intellectual activity but also a means of ethical reflection and character development.